Implikasi Pendidikan Menurut QS Ali Imran Ayat 35-37 tentang Cara Nabi Zakariya dalam Mendidik Anak Perempuan - Dienan Shafyah Zahrah; Fitroh Hayati (Jurnal Riset Pendidikan Agama Islam, 2021)
Abstract. Being a parent is closely related to caring for, nurturing and educating children. Children are a mandate from God to parents for them to always take care, nurture and educate. Parents must be fair to all children, whether they are male or female. They are not treat them differently. The purpose of this research is to find out the educational implications of QS Ali Imran verses 35-37 on how The Prophet Zakariya taught Maryam on girls educating with the following details: (1) finding out the opinions of the mufasirs on the Prophet Zakariya’s practices in educating girls from QS Ali Imran verses 35-37, (2) the essence contained in QS Ali Imran verses 35-37, (3) the opinion of education experts on education for girls , and (4) the educational implications of QS Ali Imran verses 35-37 on the Prophet Zakariya’s practices on educating girls. The research method used in this study is a descriptive method with the qualitative approach. Whereas for data collecting is technique is literature study. The author used the method of tahlili interpretation approach,namely: describing the meaning contained by the Qur'an, verse by verse in accordance with the order in the mushaf. The content of QS Ali Imran verses 35-37 according to mufassirin is: parents must educate their children in terms of obedience to Allah SWT and provide education to children in order to be a righteous and shalehah child, because the most noble man in the eyes of Allah SWT is a person who fears Him (male or female), not based on gender. The results of the study of QS Ali Imran verses 35-37 are: (1) parents should educate their children in terms of obedience to Allah Almighty, (2) education is given not based on gender, (3) parents must provide the best education for their children, and (4) an educator must provide good education and care. The educational implications contained from QS Ali Imran verses 35-37, namely: (1) parents must educate children to obey Allah Almighty, (2) parents must give the equality of rights of education for children, (3) parents mus be just to all children (male or female) in terms of education, and (4) educators must consider ways to provide education to female learners. Abstrak. Menjadi orang tua erat kaitannya dengan mengurus, mengasuh dan mendidik anak. Anak merupakan titipan dari Allah Swt bagi orang tua untuk senantiasa mengurus, mengasuh juga mendidik anak-anaknya. Orang tua haruslah bersikap adil kepada semua anak, entah itu laki-laki ataupun perempuan. Jangan sampai ada perbedaan perlakuan dari orang tua terhadap anak-anaknya. Tujuan penelitian ini adalah untuk mengetahui implikasi pendidikan dari QS Ali Imran ayat 35-37 tentang cara Nabi Zakariya dalam mendidik anak perempuan dengan perincian berikut: (1) mengetahui pendapat para mufasir tentang cara Nabi Zakariya dalam mendidik anak perempuan dari QS Ali Imran ayat 35-37, (2) esensi yang terkandung dalam QS Ali Imran ayat 35-37, (3) pendapat para ahli pendidikan mengenai pendidikan bagi anak perempuan, dan (4) implikasi pendidikan dari QS Ali Imran ayat 35-37 tentang cara Nabi Zakariya dalam mendidik anak perempuan. Metode penelitian yang digunakan ole penulis pada penelitian ini adalah metode deskriptif dengan pendekatan kualitatif dan teknik studi literatur. Penulis menggunakan metode pendekatan tafsir tahlili yaitu: menguraikan makna yang dikandung oleh al-Qur’an, ayat demi ayat sesuai dengan urutannya di dalam mushaf. Isi kandungan QS Ali Imran ayat 35-37 menurut mufassirin adalah: orang tua harus mendidik anaknya dalam hal kepatuhan kepada Allah SWT, memberikan pendidikan kepada anak supaya menjadi anak yang shaleh dan shalehah. Sebab, manusia yang paling mulia di mata Allah SWT merupakan orang yang bertakwa kepada-Nya (laki-laki maupun perempuan) bukan berdasarkan dari jenis kelaminnya. Hasil penelitian dari QS Ali Imran ayat 35-37 adalah: (1) orang tua harus mendidik anaknya dalam hal kepatuhan kepada Allah Swt, (2) pendidikan diberikan bukan berdasarkan jenis kelamin, (3) orang tua harus memberikan pendidikan yang terbaik untuk anaknya, dan (4) seorang pendidik harus memberikan pendidikan dan pengasuhan yang baik. Adapun implikasi pendidikan yang terdapat dari QS Ali Imran ayat 35-37, yaitu: (1) orang tua harus mendidik anak supaya taat kepada Allah Swt, (2) hak pendidikan bagi anak, (3) berbuat adil kepada semua anak (laki-laki ataupun perempuan) dalam hal pendidikan, dan (4) cara-cara pendidik memberikan pendidikan kepada peserta didik perempuan.